(untitled) (Journal Of Educational and Psychological Researches, 2013)
What a nation seeking to occupy a prominent place among the nations not and attached the educational process of the great interest from which you can build a conscions generation represented in the culture first, then unable to adapt to modern technology data on the labor market second . So it was for the administration a major role in the educational process and that all the evaluation of texture development of education in his administration , it is through the development of administrative paper work can be judged or under developed society , evaluation of any system depends on the efficiency of his administration in dealing with the inputs of the education system. Administration is no longer in accordance with each individual performance can the required efficiency, it has become anote of his assets , rules and art needs to be exercised to the qualities and character traits and special mentality, they have a massage ethics and traditions derived from education . The most important findings of researcher : The professional ethics for managers of all kinds and fields are available and well realized , and that the availability of these ethics is a key factor for the success of managing director in his work and success in the management of the institute thus lead to higher their level of achievement. As the faculty members do not see to their manager on the basis of sex ,but on the basis of what have the efficiency and effectiveness of administration work ,as well as the managers have the ability to leadership and management to keep pace with scientific and technological developments on one hand ,and social and economic developments in the community in order to prepare a generation of teachers able to advance the teaching-learning process and adapt to the labor market on the other hand.